2010
DOI: 10.1111/j.1872-034x.2009.00580.x
|View full text |Cite
|
Sign up to set email alerts
|

Antiangiogenesis gene armed tumor‐targeting adenovirus yields multiple antitumor activities in human HCC xenografts in nude mice

Abstract: The oncolytic virus with antiangiogenesis gene driven by the chimeric promoter has an improved killing efficacy on tumor cells, and may be useful for cancer gene therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 31 publications
(57 reference statements)
0
14
0
Order By: Relevance
“…Previous studies confirmed the antitumor activity of various vectors carrying cytokine genes, such as interferons (Belardelli & Gresser, 1996), tumor necrosis factors (Zhang et al, 1996), drug-sensitive gene HSV-tk (Steele, 2000), antiangiogenesis genes (Fang et al, 2010). When these therapeutic genes were inserted into the genome of CRAds, they were selectively and highly expressed in cancer cells as a result of the cancer-selective replication of CARds, which further enhanced therapeutic effect targeting cancer cells without toxicity to normal tissues or cells.…”
Section: Utilization Of Antitumor Transgenesmentioning
confidence: 78%
See 2 more Smart Citations
“…Previous studies confirmed the antitumor activity of various vectors carrying cytokine genes, such as interferons (Belardelli & Gresser, 1996), tumor necrosis factors (Zhang et al, 1996), drug-sensitive gene HSV-tk (Steele, 2000), antiangiogenesis genes (Fang et al, 2010). When these therapeutic genes were inserted into the genome of CRAds, they were selectively and highly expressed in cancer cells as a result of the cancer-selective replication of CARds, which further enhanced therapeutic effect targeting cancer cells without toxicity to normal tissues or cells.…”
Section: Utilization Of Antitumor Transgenesmentioning
confidence: 78%
“…The CRAd, AdSu-hE, in which a chimeric promoter of HER2 enhancer and hTERT promoter was used to drive the E1a gene, a cytomegalovirus promoter to control the human endostatin gene. In vivo intratumoral delivery of the CRAd to pre-established hepatocellular carcinoma tumors in nude mice induced a significant tumor reduction and, in some cases resulted in a complete tumor regression (Fang et al, 2010). Canstatin, a novel matrix-derived inhibitor of angiogenesis, was described as being at least 10-fold more active than endostatin (Kamphaus et al, 2000;Narazaki & Tosato, 2006).…”
Section: Crad With Antiangiogenesis Genementioning
confidence: 99%
See 1 more Smart Citation
“…Many transgenes used to arm adenoviral vectors are designed to modify the tissue architecture. For instance, vectors that degrade the extracellular matrix, 6,7,33 inhibit the angiogenesis [34][35][36][37] or target the stromal cells 29 have been constructed. The CAM model is probably relevant to study such vectors.…”
Section: Discussionmentioning
confidence: 99%
“…This includes tumor-specific promoters which are used to drive the early viral gene, chimeric fibers which are constructed to improve infection efficacy, and viral genes which are deleted to prevent oncogene activation. The human telomerase reverse transcriptase promoter (TERTp) (5,6), hypoxia response elements (HRE)-containing promoter (7) and survivin promoter (8) are present in various cancer cells. Moreover, a human α-fetoprotein (AFP) promoter has also been used in AFP-producing cells (9,10) and a cyclooxygenase-2 (Cox2) promoter (11,12) used in cells overexpressing Cox2.…”
Section: Introductionmentioning
confidence: 99%